2014
DOI: 10.1080/21501203.2014.889769
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of aflatoxigenicAspergillusand other fungi in millet and sesame from Plateau State, Nigeria

Abstract: Sixteen fonio millet and 17 sesame samples were analysed for incidence of moulds, especially aflatoxigenic Aspergillus species, in order to determine the safety of both crops to consumers, and to correlate aflatoxin levels in the crops with levels produced by toxigenic isolates on laboratory medium. Diverse moulds including Alternaria, Aspergillus, Cercospora, Fusarium, Mucor, Penicillium, Rhizopus and Trichoderma were isolated. Aspergillus was predominantly present in both crops (46–48%), and amongst the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
19
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 29 publications
7
19
1
Order By: Relevance
“…As observed in this study, the conventional method (YES and β-CDNRDCA) aided the effective discrimination of the toxigenic strains of Aspergilli compared to the sole use of the molecular assay. However, this observation is in agreement with the previous reports on the inadequacy of the use of only molecular method in the identification of aflatoxin producers [21,29,41,42]. The formation of only yellow pigment and fluorescence by Aspergillus strains have been reported not to be a reliable means of identifying aflatoxin-producing strains of Aspergilli.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As observed in this study, the conventional method (YES and β-CDNRDCA) aided the effective discrimination of the toxigenic strains of Aspergilli compared to the sole use of the molecular assay. However, this observation is in agreement with the previous reports on the inadequacy of the use of only molecular method in the identification of aflatoxin producers [21,29,41,42]. The formation of only yellow pigment and fluorescence by Aspergillus strains have been reported not to be a reliable means of identifying aflatoxin-producing strains of Aspergilli.…”
Section: Discussionsupporting
confidence: 92%
“…Hence, the need to combine both the conventional with the molecular method. The observation of the failure of isolates FG27, FG35, FG37, FG38, FG32, and FG45 to produce fluorescence under UV-light despite the positive expression of aflatoxin biosynthesis pathway genes is in conformity with previous reports [21,42] where authors reported a similar observation in some Aspergillus strains isolated from Cashew nuts, millet, and sesame grains in Nigeria, respectively. A bright blue fluorescence is usually achieved when a reaction exists between a produced aflatoxin and hydrophobic β-cyclodextrin which is capable of fluorescing under UV-light [43].…”
Section: Discussionsupporting
confidence: 91%
“…For cultures from Nigeria, food (local rice, maize, mushroom, peanut cake and sesame) samples from various markets and agricultural soil samples from the top 2 cm of the soil were collected between October 2010 and February 2012. Cultures from food samples, except those from local rice and maize, were reported in other studies ( Ezekiel et al., 2013a , Ezekiel et al., 2013b , Ezekiel et al., 2014 ). The isolates were previously reported as unnamed taxon S BG based on phenotype (macro- and microscopic characters on 5/2 agar (5 % V-8 juice and 2 % agar, pH 5.2)) and aflatoxin production (on neutral red desiccated coconut agar) or A. parvisclerotigenus based on ITS, β-tubulin and calmodulin gene sequences.…”
Section: Methodsmentioning
confidence: 78%
“…This profuse sporulation may account for the ease with which some species are isolated. Very common indoor Aspergillus species include A. calidoustus , A. flavus (common aflatoxin producers; Codner et al. 1963, Schroeder & Boller 1973, Pildain et al.…”
Section: Introductionmentioning
confidence: 99%